P53 and Ki-67 expression in renal cell carcinomas of pregnant women and their correlation with prognosis: a pilot study. Issue 1 (1st January 2008) - Pomara, G; Salinitri, G; Nesi, G; Maio, E; Minervini, A; Gammazza, A. M; Francesca, F; Cappello, F; Selli, C
Abstract : In the present study, we reported two cases of renal cell carcinoma (RCC) diagnosed in pregnant women (Pt) that were submitted to radical nephrectomy, in both cases within the fourth month. The patients, after 13 and 3 years, respectively, did not show evidence of recurrent disease. We performed an immunohistochemical study on RCC specimens in comparison to seven age-matched controls (Cl). The panel of antibodies included Ki-67, p53, bcl-2, ER, PgR, PCNA, and IGF-1. We describe a difference in the expression of p53 and Ki-67. Specifically, p53 was highly expressed in RCC of both Pt but scarcely present or absent in Cl; by contrast, Ki-67 was hardly expressed or negative in RCC of both Pt, being commonly positive in Cl. These results may correlate with a good outcome of the disease in Pt. Although the limited number of cases did not permit any statistical evaluation, we postulate that these differences have not to be underestimated since they may disclose a correlation between pregnancy and biological behavior of tumoral disease. Further study may (dis)prove this hypothesis.